Blind Image Quality Assessment with Image Denoising: A Survey (Journal of Pharmaceutical Negative Results, 2022)
The quality of an image is most important at every stage of its processing. Images captured with recent smart devices such as digital cameras or smart mobile phones can be affected by various types of noise, which degrades image quality. The evaluation and elimination of noise or distortion in a picture is viewed as significant as, the evaluation of the image's quality. This study presents a survey of available techniques and algorithms for denoising images and determining image quality. This paper studies the types of noise or distortions, techniques, parameters used by the algorithm, various metrics used to assess the quality and the performance of the algorithm. Some of the important filters, databases in the area of image quality assessment and denoising are discussed in this paper.